Characterization of immunomodulatory responses induced by manuka honey - Masad, Razan J.; Nasser, Rasha A.; Bashir, Ghada; Mohamed, Yassir A.; Al-Sbiei, Ashraf; Al-Saafeen, Besan H.; Fernandez-Cabezudo, Maria J.; Al-Ramadi, Basel K. (Frontiers in Immunology, 2022)
Manuka honey (MH) is known for its wound-healing, anti-microbial, anti-oxidant and anti-tumor properties. However, there is conflicting evidence regarding the role of MH in inflammatory responses, with some studies highlighting its proinflammatory capacity and others showing that it has a predominantly anti-inflammatory activity. The current study is aimed at characterizing the immunomodulatory capacity of MH using both in vitro and in vivo approaches, focusing on the underlying mechanisms. Treatment of RAW 264.7 macrophages with 1% MH (w/v) resulted in a significant increase in gene expression ( 18-fold) and protein level ( 30-fold) of tumor necrosis factor-alpha (TNF-). Similarly, an increase was observed in the expression of other inflammatory cytokines including interleukin-1β (IL1-), interleukin-6 (IL-6), and inducible nitric oxide synthase (iNOS), as well as the chemokines; (C-X-C motif) ligand 2 (CXCL2) and (C-C) motif ligand 2 (CCL2) . Using an in vivo model, intraperitoneal (i.p.) administration of MH in C57BL/6 mice elicited a peritoneal response characterized by a significant expansion in the number of peritoneal exudate cells (PECs), which was mainly due to a 35-fold increase in the recruitment of neutrophils. Importantly, this response was evident in toll-like receptor 4 (TLR4)-defective C3H/HeJ mice, indicating that the observed stimulatory effect occurs independently of TLR4 and unlikely to be mediated by any LPS contaminant. MH administration also led to changes in the phenotypic expression and functional maturation of peritoneal macrophages, as evidenced by a shift towards the CD11blo F4/80lo phenotype and an increase in the expression of major histocompatibility complex (MHC) class II proteins. In contrast, the MH-initiated peritoneal response was largely abrogated in mice deficient in myeloid differentiation primary response 88 (MyD88) protein, a critical adaptor of most TLR signaling pathways. Thus, the current findings help to characterize the immunostimulatory properties of MH and their dependence on TLR signaling, and highlight the potential utility of MH as an immunomodulatory agent in a variety of disorders.